1994
DOI: 10.2307/1937462
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Larval Density on Adult Demographic Traits in Ambystoma Opacum

Abstract: Factors that affect traits of aquatic larvae of amphibians may have long—lasting effects on terrestrial juveniles and adults. I manipulated larval densities of marbled salamanders, Ambystoma opacum, in large—scale field enclosures during 2 yr, released the juveniles that metamorphosed from these enclosures, and tested for effects on adults that returned to the pond during 6—7 subsequent breeding seasons. Individuals from low larval density treatments tended to have greater lipid stores at metamorphosis than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
288
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(304 citation statements)
references
References 65 publications
(82 reference statements)
10
288
2
1
Order By: Relevance
“…The most pervasive sublethal effects of Hg we observed were reductions in larval and juvenile body size. Because smaller size at metamorphosis can delay maturation (Berven 1990, Scott 1994, we incorporated this sublethal effect by reducing the proportion of female B. americanus that matured at age three vs. age four. Somewhat surprisingly, we found that delaying maturation by up to one year had little effect on adult population size or extinction probability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most pervasive sublethal effects of Hg we observed were reductions in larval and juvenile body size. Because smaller size at metamorphosis can delay maturation (Berven 1990, Scott 1994, we incorporated this sublethal effect by reducing the proportion of female B. americanus that matured at age three vs. age four. Somewhat surprisingly, we found that delaying maturation by up to one year had little effect on adult population size or extinction probability.…”
Section: Discussionmentioning
confidence: 99%
“…For each scenario, we adjusted survival parameters based on all observed effects of Hg on survival or embryonic viability (Table 1). Because the most pervasive sublethal Hg effects we observed were reductions in larval and juvenile body size, and because smaller size at metamorphosis can delay maturation (Berven 1990, Scott 1994, we incorporated this sublethal effect by reducing the proportion of female B. americanus that matured at age three vs. age four (q) by the observed reduction in growth rate. For these initial simulations, we assumed that sublethal reductions in body size had no positive or negative effect on other post-metamorphic individuals in the population.…”
Section: Evaluating Effects Of Maternally Transferred and Dietary Hgmentioning
confidence: 99%
“…For organisms with complex life histories, processes that occur during early juvenile or larval stages, such as density dependent competition or delayed metamorphosis, may lead to deleterious effects later in the organisms life cycle (Pechenik 2006). Linking larval density to adult fitness has been accomplished across many taxa, predominantly in the insects and anurans (Scott 1994, Juliano 1998, à Maximal models, with different slopes for each caging treatment, were examined and found not to be appropriate for all size classes (see Methods).…”
Section: Discussionmentioning
confidence: 99%
“…Although we cannot totally exclude the possibility that maternal effects drive size at metamorphosis in altitude, it seems unlikely because larger individuals are usually observed in altitudes (for B. bufo : Hemelaar, 1988;Miaud and Merilä, 2001;Morrisson and Hero, 2003) that should instead lead to larger offspring and no further maternal effects have been detected in low-altitude populations (Supplementary Figure S1; Supplementary Table S2). Smaller sizes of fast-developing genotypes instead suggests a negative genetic correlation between these traits, and then a fitness cost to develop faster because large size at metamorphosis generally confers higher fitness through improved juvenile survival (for example, Berven, 1990;Goater, 1994;Altwegg and Reyer, 2003) and higher adult reproductive success (for example, Scott, 1994;Altwegg and Reyer, 2003). Although this trade-off can arise from a selection against fast development in altitude, it may also contribute to the growth rate divergence along altitudinal gradient.…”
Section: Local Adaptation To Altitudementioning
confidence: 99%